A Review of Hybrid Battery Management System (H-BMS) for EV - Nur Huda Mohd Amin; Mohd Ruddin Ab Ghani; Auzani Jidin; Zanariah Jano; Tole Sutikno (Universitas Ahmad Dahlan, 2018)
Significant to a major pollution contributor in passenger vehicles, electric vehicles are more acceptable to use on the road. Electric Vehicles (EVs) burn energy based on the usage of the battery. The usage of the battery in EVs is monitored and controlled by Battery Management System (BMS). A few factors monitor and control Battery Management System (BMS). This paper reviewed the battery charging technology and Remote Terminal Unit (RTU) development as a Hybrid Battery Management System (H-BMS) for Electric Vehicle (EV).